Common currency decisions: some implications for Barbados. - CODRINGTON, Harold (1995)
Identifies concerns about the conversion to the Caribbean dollar as well as the parity and stability of that unit. Notes that some of the more contentious issues with which Barbadians may have to grapple are the harmonisation of macro-economic policies, labour mobility and closer political union.